REALISTIC MATHEMATICS EDUCATION (RME) ASSISTED WITH SCAFFOLDING TO ENHANCE MATHEMATICAL REASONING - Mutafarida, Mutafarida; Amir, Mohammad Faizal (IJIET (International Journal of Indonesian Education and Teaching), 2026)
Until recently, the educational curriculum has led to the need for problem-solving through adequate mathematical reasoning. In addition, there is much evidence that problem-solving is achieved through mathematical reasoning. The problem is that primary students' mathematical reasoning is still low. Meanwhile, many empirical studies state that Realistic Mathematics Education (RME) can enhance mathematical reasoning. On the other hand, scaffolding is a solution that helps achieve learning outcomes, including mathematical reasoning. This study examines the impact of RME assisted with scaffolding toward students' mathematical reasoning. The research method was quasi-experimental with a non-equivalent (pre-test and post-test) control-group design. The study sample involved fifth-grade students using a purposive sampling technique. The data analysis used was an independent sample t-test. The study's findings showed that RME assisted with scaffolding, which affected students' mathematical reasoning. Another finding was that students' primary mathematical manipulation as part of mathematical reasoning increased significantly. Therefore, integrating RME and scaffolding can be a new alternative learning strategy to enhance primary students' mathematical reasoning.